Indian power projection ambition, arms and influence - Joshi, Shashank (Whitehall paper, 2015)
India is growing into one of Asia's most important military powers. Its defence budget has more than doubled in the past decade, and it imports more arms than anyone else in the world. But India is still seen as a land power focused on long, disputed and militarised borders with Pakistan and China rather than the global military force it was in the first half of the twentieth century under British rule. Is this changing? India is acquiring increasing numbers of key platforms - aircraft carriers, amphibious ships, refuelling tankers and transport aircraft - that are extending its reach to the Indian Ocean littoral and beyond. But most accounts of this build-up have been impressionistic and partial